ANALISIS STRATEGI KOMUNIKASI PEMASARAN DALAM VIDEO ENDORSEMENT INFLUENCER ARIEF MUHAMMAD DAN TASYA FARASYA DI INSTAGRAM FEEDS - Hertantiningsih, Tifanny; Wibowo, S. Kunto Adi; Fuady, Ikhsan (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
The high number of Instagram users caused many producers of goods and services choosing to promote their products through endorsement services carried out by social media influencers. This marketing strategies using influencers is so important because it can help producers of goods and services to create a positive product image by word of mouth and can meet business goals between the two parties. Based on this phenomenon, this study aims to determine the marketing strategies used by Influencers Arief Muhammad and Tasya Farasya, then comparing the number of likes and comments in endorsement videos uploaded on Instagram Feeds that using three types of marketing strategies, namely boasting of company, discount codes, and use of product, both verbally and non-verbally. This study observed as many as 57 endorsement video content obtained from the calculation of the Slovin’s formula, and the hypothesis was testing by using descriptive quantitative content analysis methods and non-parametric inferential statistics. The data collection in this study was carried out by observing the upload of influencer's endorsement videos on the use of marketing strategies in Instagram Feeds which were then coded using a coding book.